2017
DOI: 10.1016/j.jtcme.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of yoga program on executive functions of adolescents dwelling in an orphan home: A randomized controlled study

Abstract: Executive function (EF) is important for physical and mental health of children. Studies have shown that children with poverty and early life stress have reduced EF. The aim of the study was to evaluate the effect of Yoga program on the EF of orphan adolescents. Seventy two apparently healthy orphan adolescents randomized and allocated into two groups as Yoga group (n = 40; 14 girls, age = 12.69 ± 1.35 yrs) and Wait List Control (WLC) group (n = 32, 13 girls, age = 12.58 ± 1.52 yrs). Yoga group underwent three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 62 publications
2
14
1
3
Order By: Relevance
“…Yoga was effective in improving delayed recall of spatial information and verbal memory in 11–16-year-old children (Manjunath and Telles, 2004). Similar results were reported for three months of yoga practice on executive functions of adolescent dwelling in an orphan home (Purohit and Pradhan, 2016). Yoga practice was an effective tool when working with students with Down syndrome, cerebral palsy, autism, sensory integration disorder, learning difficulties (Galantino et al, 2008), and attention deficit hyperactivity disorder (Balasubramaniam et al, 2012).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Yoga was effective in improving delayed recall of spatial information and verbal memory in 11–16-year-old children (Manjunath and Telles, 2004). Similar results were reported for three months of yoga practice on executive functions of adolescent dwelling in an orphan home (Purohit and Pradhan, 2016). Yoga practice was an effective tool when working with students with Down syndrome, cerebral palsy, autism, sensory integration disorder, learning difficulties (Galantino et al, 2008), and attention deficit hyperactivity disorder (Balasubramaniam et al, 2012).…”
Section: Introductionsupporting
confidence: 86%
“…Yoga is suggested to be an effective sensory-motor training for children to reduce behavioral and emotional problems and improve cognitive functions which might have a positive impact on academic performance (Chaya et al, 2012; Chou and Huang, 2017; Bazzano et al, 2018; Cohen et al, 2018). Recent studies demonstrated that yoga is one intervention with the potential to increase attention and academic performance in children (Chaya et al, 2012; Khalsa et al, 2012; Noggle et al, 2012; Chou and Huang, 2017) and adolescents (Khalsa et al, 2012; Noggle et al, 2012; Purohit and Pradhan, 2016). Yoga practice includes stretching postures, breathing exercises, and meditation (Taimini, 2005; Brethenoux-Seguin, 2007; Rosen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Further, regulation of the speed-accuracy tradeoff within the three components of executive control might be the unifying mechanism through which yoga training is influential. Studies examining the effect of mindfulness-related practice on cognitive task performance report either speed (RT) or accuracy, but not both, as in the case with working memory tasks (e.g., Jella and Shannahoff-Khalsa, 1993;Jyothsna and Rao, 2014;Sharma et al, 2014;Johnson et al, 2015;Jansen et al, 2017;Purohit and Pradhan, 2017;Crivelli et al, 2018), planning and cognitive flexibility (e.g., Levine et al, 2011;Kiani et al, 2016), and inhibitory control (e.g., Lakey et al, 2007;Semple, 2010;Alfonso et al, 2011;Moore et al, 2012;Kiani et al, 2016;Wimmer et al, 2016). Results suggest that analyzing speedaccuracy tradeoff might be useful in exploring the unifying mechanism by which yoga and other mindfulness practices might enhance executive control.…”
Section: Discussionmentioning
confidence: 99%
“…Non-posturerelated training combined with goal training for substance abuse also reveals no improvement to verbal working memory among a trained group (Alfonso et al, 2011), or there is a weak link between posture control and verbal working memory (Telles et al, 2007(Telles et al, , 2008. However, studies using a combined analysis of postures and breathing make it difficult to delineate training-induced improvement in verbal working memory (e.g., Purohit and Pradhan, 2017). Results might be suggestive of a selective link between pranayama breathing and verbal working memory possibly because verbal working memory (digit span task) implicates the phonological loop (Wang and Bollugi, 1994;Christie et al, 2013) and is associated with the respiratory process of breath control (Lau et al, 2015).…”
Section: Working Memorymentioning
confidence: 99%
“…These persons also experienced lower stage fright. The positive effect of yoga on executive functions 4 was observed in adolescents who underwent a three months yoga traing (Purohit and Pradhan. 2016).…”
Section: Cognitive Functionsmentioning
confidence: 99%